Profitabilitas Pemoderasi Determinan Pengungkapan Modal Intelektual - Mukhibad, Hasan; Setyawati, Meyliani Eka (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019), 2019)
This research aims to analyze the effect of age, size, managerial ownership, and leverage on Intellectual Capital Disclosure (ICD) with earnings per share as a moderating variable. The population of this research is companies listed on the LQ 45 Index. The sampling method used to determine the samples of this research is purposive sampling, in the observation year 2014-2017. The research samples are 26 companies with 104 units of analysis. The data are then analyzed using moderation regression analysis with the absolute difference value test. The results are indicate that age, size, and managerial ownership have a positive effects on ICD, while the leverage does not.  Further, companies' profitability could strengthen the correlation between size and ICD but weaken toward the correlation between managerial ownership and ICD. Keywords: Managerial Ownership; Financial performance; Leverage; Disclosure of Intellectual Capital.